Flexible males, proactive females: increased boldness/exploration damping with time in male but not female colonists - Andrey V. Tchabovsky; Elena N. Surkova; Ludmila E. Savinetskaya; Ivan S. Khropov (Royal Society Open Science)
Individuals colonizing new areas during range expansion encounter challenging and unfamiliar environments, suggesting that colonists should differ in behavioural traits from residents of source populations. The colonizer syndrome is supposed to be associated with boldness, exploration, activity and low sociability. We assessed spatial and temporal variation of the colonizer syndrome in an expanding population of midday gerbils (Meriones meridianus). Male-first colonists did not differ significantly from residents of the source population, whereas female-first colonists were bolder, faster and more explorative than females from the source population. These findings support a boldness/exploration syndrome as a typical colonizer trait, which appears to be restricted to females in midday gerbils. Males and females also differed in behavioural dynamics after colony establishment. In males, boldness/exploration/sociability peaked in newly founded colonies, then sharply decreased in subsequent generations consistently with decreasing environmental uncertainty in ageing colonies. In females, greater boldness/exploration did not diminish with time post-colonization, i.e. female colonists retained the bold/explorative phenotype in subsequent generations despite facing a less challenging environment. Thus, female colonists, unlike males, carry a specialized behavioural colonizer phenotype corresponding to a proactive behavioural coping strategy. We link sex differences in behavioural traits of colonists to sex-specific life-history strategies.